Tragedy, History, and Ecstasy: Concerning Nietzsche’s “Untimely” Ideas on Authentic Selfhood - Pasco, Marc Oliver D. (Archīum Ateneo, 2015)
This paper proposes that there exists a specific philosophical connection between Nietzsche’s thoughts on tragedy in Birth of Tragedy and his thoughts on history in “On the Uses and Disadvantages of History for Life.” The paper hopes to enrich one’s appreciation of Nietzsche’s early ideas on authentic selfhood by showing the relation between Dionysiac ecstasy and unhistorical consciousness. A postscript in the last part of the paper examines Philippine folk religiosity within the framework of the aforementioned connection between Dionysiac ecstasy and unhistorical consciousness.